Target Penyelesaian Pendidikan S1 Bagi Mahasiswa Penerima Beasiswa Kader Muhammadiyah Tahun 2011-2012(StudiKasus di UniversitasMuhammadiyah Surakarta) - Susanti, Ika, Dr. Mutohharun Jinan, M.Ag (2017)
Muhammadiyah is an organization that was established in November 18, 1912. Cadrerization in Muhammadiyah is a structured program that aims to prepare the organization's successors of the future. Based on this background, this study aims to uncover the target of undergraduate completion for the Cadre Scholarship awardees as well as the driving and inhibiting factors in completing the education target above. This research is a field research with a qualitative descriptive approach. First, data are obtained through interview, documentation, observation, and sample are taken from population by purposive tecnique. Later, they were analyzed with qualitative descriptive method.Through analysis of the research data, the writer concludes that. First, University of Muhammadiyah Surakarta provides educational aids to Muhammadiyah cadres who are taking a course at University of Muhammadiyah Surakarta in the form of a excellent scholarship. Second, In undergoing the course, the cadres face a variety of factors that could hinder the completion of S1, such as the absence of tuition fees from parents, the difficulty in managing time between attending lecture and joining organization, the demand in achieving the minimum GPA target at some departments, and the need to meet the daily necessities that have not been charged in the scholarships given. Third, awardees feel helped by factors contributing to the success of S1 completion target, e.g. the availability of tuition fees over eight semesters and the recruitment opportunity for potential cadres affairs in both academic and organization. Forth, In this study, the scholarship awardees as the research subjects are divided into three types, namely; students who have completed their S1 education, students who are still in the process of their S1 completion, and students who are drop out and never finish their S1 education.